Origin and evolution of serpentinized peridotite from the Ciletuh Mélange in Sunda Arc, Indonesia: Evidence from petrography, mineralogy, and geochemistry - Ikhram, Rinaldi; Hoshide, Takashi; Ohba, Tsukasa; Rosana, Mega Fatimah; Hardiyono, Adi (Journal of Asian Earth Sciences: X, 2025)
•The Ciletuh Ophiolite features serpentinized peridotite in varying degrees.•Serpentinite types include lizardite, antigorite, chrysotile, and polygonal serpentine.•The peridotite protolith originates from both magmatic cumulates and mantle sources.•Spinel Cr# and olivine Fo# suggest diverse origins, including abyssal and supra-subduction.•Rodingite dikes show evidence of additional metasomatic processes. The Ciletuh Mélange in southern Sundaland (West Java, Indonesia) is a key location for ophiolitic mélanges, featuring widespread serpentinized peridotite. These rocks exhibit varied textures and structures and can be classified into three types based on the extent of serpentinization: type 1 (lherzolite, <10 % serpentinization), type 2 (60–80 % serpentinization), and type 3 (>90 % serpentinization). Olivine and spinel mineral chemistry indicates two origins for the peridotite: magmatic cumulate (type 1, olivine Fo#: ∼81, spinel Cr#: 63–70) and mantle-derived (types 2 and 3, olivine Fo: 88–90, spinel Cr#: 55–66). Protoliths of both types 2 and 3 show abyssal (mid-oceanic ridge basalt) and fore-arc mantle peridotite characteristics, formed by partial melting (∼5–25 %) and melt-rock interaction (TiO2 in spinel > 1 wt%). Type 1 lherzolite, by contrast, crystallized as a cumulate at the mantle-crust boundary. The variation of geochemical signatures, along with evidence of melt influence, suggest formation in a supra-subduction zone. In subduction systems, the protoliths underwent serpentinization at varying metamorphic grades, producing serpentines such as lizardite, antigorite, chrysotile, and polygonal serpentine. Antigorite formed under high-grade metamorphism, while lizardite, chrysotile, and polygonal serpentine form under lower-grade conditions. The presence of rodingite dikes cutting through serpentinite suggests metasomatic processes, notably rodingitization, involving diffusional metasomatism between serpentinization fluids and metamorphosed gabbro in the subduction zone. Serpentinized peridotites and rodingites were later exhumed as part of the ophiolitic mélange.